Research in the history of economic thought and methodology. Volume 35, part A - Fiorito, Luca, 1967-; Scheall, Scott; Suprinyak, Carlos Eduardo (Emerald Publishing Limited, 2017)
Volume 35A of Research in the History of Economic Thought and Methodology features a symposium on historical epistemology, guest edited by Till Düppe and Harro Maas. The symposium includes new research from the guest editors, as well as from Loïc Charles and Christine Théré, Hsiang-Ke Chao, Tobias Vogelsang, and Thomas Stapleford. This internationally renowned cast of contributors offers a variety of perspectives on one of the major approaches in empirical philosophy of science and economic thought. Volume 35A also includes a new research paper by Cameron Weber on the paradoxical notion of value employed in the economics of art and culture. An archival piece by Marc Nerlove, winner of the John Bates Clark Medal in 1969, completes the volume. Originally written in the summer of 1953, when Nerlove was a 19-year-old graduate student serving as research assistant to Jacob Marschak and Tjalling Koopmans at the Cowles Commission, the paper relates the ideas of Cournot to the concept of Nash equilibrium. The paper was long-forgotten by Nerlove and has only recently been rediscovered among the Marschak Papers at UCLA. Olav Bjerkholt contributes a foreword to Nerlovés archival piece.
Including a symposium on the historical epistemology of economics.
Includes index.
Keywords: Economic history.; Business & Economics -- Economic History.; Economic theory & philosophy.; elektronické knihy; electronic books